(untitled) (Al-Farooq Journal of Sciences, 2026)
This review provides a comprehensive quantitative and systematic analysis of the development of spray-deposited, doped, and co-doped cadmium sulfide thin films used as optical windows in solar cells during the period from 2015 to 2025. Based on 25 peer-reviewed studies, this work classifies a wide range of dopers into: Group III elements (aluminum, gallium, indium), Group I acceptors (sodium, silver, copper), transition metals (barium, nickel, cobalt, manganese, zinc), rare earth elements (europium, praseodymium, dysprosium), and synergistic co-doping systems (aluminum-sodium, gallium-potassium, magnesium-cobalt, tin-zinc, aluminum-lanthanum). Analysis of variation reveals that the resulting stable hexagonal phase (wurtzite) is present in 72.0% of published studies. Quantitative scanning spectroscopy identifies an optimal doping window at μ=3.00 atomic. With an ±0.81% (σ=±0.81% atomic), this achieves a blueshift in the optical band gap (according to Burstein-Moss) averaging 2.45 eV (σ=±0.02 eV) and a transparency of 70–85%. Exceeding this value leads to the deposition of amorphous secondary phases at the grain boundaries, generating lattice stress and a 56.0% reduction in grain size (<30 nm). Donor doping (aluminum, fluorine) yielded the best results in conductivity and device efficiency, while rare-earth elements (dysprosium, praseodymium, europium) improved the performance of the photodetectors. However, the data revealed a critical gap in transport data (0.0% for Hall kinetics measurement) and widespread neglect (88.0%) of long-term environmental degradation protocols.